IMPLEMENTASI METODE PEMBELAJARAN TAHFIZH BAGI MURID BAIT QURANY SALEH RAHMANY (BQSR) BANDA ACEH - Mahdalena Mahdalena (Jurnal Ilmiah Didaktika: Media Ilmiah Pendidikan dan Pengajaran, 2017)
Many teenagers in Aceh have been found to be unable to properly recite the Quran, one of which is caused by their lack of habits to reciting the Quran during childhood. To respond to this issue, a learning institution called Bait QuranySalehRahmany (BQSR) Kindergarten/Preschool in Banda Aceh works to teach the children to recite and memorize the Quran in their early years. The subjects of the study were the principal, four teachers, and several students of BQSR Banda Aceh. This study employed a qualitative research design with an analytic descriptive method. Data were collected by observation, interview, and documentation. The data were then analyzed by data reduction, data display, and data verification. The findings showed that the Quran materials to be memorized included surah An-Naas and surah An-Naba’. In terms of the methods, the school implemented the methods of kinesthetic, andJarimatika(use of fingers). The implementation of these methods was as follow: first, in the Jarimatika method, the fingers were used as the tool in helping the students memorize the surah; and second, in the kinesthetic method, the memorization was done word-by-word (juzamma), and the body movements were used while memorizing the surah. The implications of using the Jarimatika method indicated that the students were easier to memorize, their memorization could last longer, their cognitive domain was also exercised, and the motoric sensor of their hands could be stimulated. As for the kinesthetic method, the implications elucidated that the students were also easier to memorize the surah, the passive attitude of the students could be overcome, the learning atmosphere was much better, the students’ achievements were also affected, the motoric sensor of the students could also be stimulated, and the tahfiz skill of the students could be enhanced as well.